A Comment on "Populist Leaders and the Economy" - Shih-Hsien Chuang; Matthew Holian; Nathaniel Pattison; Prasanthi Ramakrishnan (Institute for Replication (I4R), 2024)
Funke, Schularick, and Trebesch (2023) investigate the impact of populist leaders on GDP growth in 60 countries. They build an original dataset identifying populist presidents and prime ministers from 1900 to 2020. They then examine changes in countries' GDP growth rates following a populist leader using various empirical methods. They find that 5-15 years after a populist leader, the GDP per capita in that country is lower. Focusing on the panel regression results (Table 2), which we replicate, the authors find a reduction in GDP growth rates of 0.8-1 percentage point per year, with p-values ranging from 0.000 to 0.023. We successfully computationally reproduce these estimates. Second, we recode the variable identifying populist leaders from the authors' source and examine the sensitivity of the estimates to changing the sample time period to include the "war" years of 1915-1945. We find that the results in our main change - using the extended time-period sample - are qualitatively similar to the original results, though with smaller and noisier point estimates. Specifically, the 5-year estimate in Table 2 column 3 changes from -0.97 (p-value 0.02) to -0.43 (p-value 0.2), and the 15-year estimate in Table 3 column 3 changes from -0.73 (p-value 0.01) to -0.53 (p-value 0.17). We then turn to sensitivity analysis regarding small differences in research choices about how to code the start of populist spells and which spells to include in the sample. We find the original results are highly robust to these changes. For example, in our Table 3 column 3, the estimated effect changes from the original -0.73 (p-value 0.01) to -0.75 (p-value < 0.01) and -0.78 (p-value < 0.01).
Keywords: 330